An 8-pixel compact focal plane array with integrated LO distribution network - Tan, B; Yassin, G (Curran Associates, 2018)
We present the design of an 8-pixel Superconductor-Insulator-Superconductor (SIS) array centred at 650 GHz, which comprises two nearly identical 1×4 planar array chips, stacked together to form a 2×4 focal plane array. The array is fed by a single local oscillator (LO) source, and the array size is extendable by either increasing the number of mixing elements in the array chip or the number of stacking. The LO and RF signals for each mixer in the array are combined on-chip via a microstrip-coplanar waveguide (CPW) crossover which allows control of the RF/LO coupling level for each mixing element. The use of this planar beam splitter enables us to simplify greatly the design of the array mixer chip, as well as the design of the mixer block, which is important for future large pixel arrays. In this paper, we describe the design of the various components of the array chip, and the design of the mixer array block including the simplified LO distribution network.